Selective exposures in orthopaedic surgery revision hip replacement - Coutts, Richard D.; American Academy of Orthopaedic Surgeons (Rosemont, ill. : American Academy of Orthopaedic Surgeons, 2003)
(Producer) This program covers: Surgical approaches for revision total hip replacement, Indications, advantages, and disadvantages for each exposure and keys to reducing risk of complications
Title from disc label
Approaved for up to 3.0 hours of AMA PRA Category 1 CME credit
System requirements: PC; Windows 9X or NT 4.0; 586 class chip, 233 mhz or higher; 32 MB RAM; 10 MB hard drive space; 2 MB video RAM; color display (800x600, 16 bit); 8X CD-ROM drive or 2nd generation DVD-ROM; Quicktime 4.0; DirectX, version 6.0 or higher; SoundBlaster compatible card w/speakers
System requirements: Macintosh OS 8.x or later; Power PC Mac; 32 MB RAM; 10 MB hard drive space; 2 MB video RAM; color display (800x600, 16 bit); 4X CD-ROM drive or 2nd generation DVD-ROM; Quicktime 4.0; Macintosh sd. system w/speakers
Keywords: Arthroplasty, Replacement, Hip -- methods; Reoperation -- methods